Pendidikan karakter Qur’ani: Analisis Kisah Nabi Ibrahim dalam QS. Al-Baqarah: 124-141 Perspektif Tafsir Al-Misbah - Abdul Ghani; Zulhamdi; Muhammad Syahrial Razali Ibrahim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Character education in contemporary Islamic education faces a persistent challenge of fragmentation between cognitive achievement, moral formation, and spiritual orientation. This article aims to examine QS. Al-Baqarah: 124–141 as a Qur’anic framework for character education pedagogy through the perspective of Tafsir Al-Misbah by M. Quraish Shihab, and to analyze its relevance for strengthening Islamic character education in modern contexts. This study employs a qualitative library research approach using thematic analysis grounded in the tafsir tarbawi framework. Primary data consist of the Qur’an and Tafsir Al-Misbah, while secondary data are drawn from reputable academic journals and scholarly works on character education and Islamic pedagogy. The analysis demonstrates that QS. Al-Baqarah: 124–141 does not merely present a collection of normative moral values, but articulates a coherent system of character education pedagogy operating through a staged and sustained process. The concept of imāmah functions as a pedagogical mechanism for character formation through moral testing; imāmah is positioned as moral leadership legitimized by proven integrity; prayer serves as an instrument of spiritual education that integrates reflective awareness and transcendental dependence within the educational process; and the emphasis on transgenerational continuity highlights the long-term orientation of Qur’anic character education. These findings indicate that the narrative of Prophet Ibrahim constitutes an integrative and process-oriented model of Qur’anic character pedagogy rather than a static moral exemplar. The novelty of this study lies in conceptualizing QS. Al-Baqarah: 124–141 as a Qur’anic character pedagogy framework grounded in prophetic leadership and transgenerational moral responsibility, moving beyond the conventional approach of moral value classification. This study contributes theoretically to Islamic character education by emphasizing pedagogical processes, moral leadership, and the sustainability of values in response to contemporary educational challenges.